High-energy particle interactions in the inner jet of the radio galaxy M87 - Guennou, Chloé (2010)
Recent observations with the High Energy Stereoscopic System (HESS) have revealedstrong and variable high-energy gamma-ray emission from the radio galaxy M87. Theorigin of such emission is uncertain, but the rapid variability indicates that it shouldbe produced close to the central engine of the source. In this work, a lepto-hadronicone-zone model is applied to the available multiwavelength data of M87. The differentenergy losses for both primary and secondary particles are calculated. Then, the differentcontributions to the spectral energy distribution through interactions with matter,radiation and magnetic fields are obtained, in good accordance with the observations.